3D bioprinting of conductive hydrogel for enhanced myogenic differentiation. Issue 5 (14th August 2021) - Wang, Ying; Wang, Qingshuai; Luo, Shengchang; Chen, Zhoujiang; Zheng, Xiang; Kankala, Ranjith Kumar; Chen, Aizheng; Wang, Shibin
Abstract: Recently, hydrogels have gained enormous interest in three-dimensional (3D) bioprinting toward developing functional substitutes for tissue remolding. However, it is highly challenging to transmit electrical signals to cells due to the limited electrical conductivity of the bioprinted hydrogels. Herein, we demonstrate the 3D bioprinting-assisted fabrication of a conductive hydrogel scaffold based on poly-3, 4-ethylene dioxythiophene (PEDOT) nanoparticles (NPs) deposited in gelatin methacryloyl (GelMA) for enhanced myogenic differentiation of mouse myoblasts (C2C12 cells). Initially, PEDOT NPs are dispersed in the hydrogel uniformly to enhance the conductive property of the hydrogel scaffold. Notably, the incorporated PEDOT NPs showed minimal influence on the printing ability of GelMA. Then, C2C12 cells are successfully encapsulated within GelMA/PEDOT conductive hydrogels using 3D extrusion bioprinting. Furthermore, the proliferation, migration and differentiation efficacies of C2C12 cells in the highly conductive GelMA/PEDOT composite scaffolds are demonstrated using various in vitro investigations of live/dead staining, F-actin staining, desmin and myogenin immunofluorescence staining. Finally, the effects of electrical signals on the stimulation of the scaffolds are investigated toward the myogenic differentiation of C2C12 cells and the formation of myotubes in vitro . Collectively, our findings demonstrate that the fabrication of the conductive hydrogels provides a feasible approach for the encapsulation of cells and the regeneration of the muscle tissue.